2022
DOI: 10.7196/samj.2022.v112i2.16040
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism risk assessment and prophylaxis in hospitalised medical patients in the Cape Town metropole, South Africa

Abstract: Background. Venous thromboembolism (VTE) is regarded as the most preventable cause of inpatient death in hospital settings globally. VTE can be prevented through the provision of non-pharmacological and/or pharmacological thromboprophylaxis following individualised risk screening. The Caprini risk assessment model (RAM) offers a validated and well-established approach for VTE risk assessment in medical inpatients. Literature findings describe a trend towards inappropriate and under-prescribing of thromboprophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This finding is supported by other studies done elsewhere. 24,28,29 In contrast, a study conducted in Iran found that old age was the most pervasive risk factor. 30 This disparity could be explained by the fact that most patients with risk factors in our study included patients who were relatively younger.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is supported by other studies done elsewhere. 24,28,29 In contrast, a study conducted in Iran found that old age was the most pervasive risk factor. 30 This disparity could be explained by the fact that most patients with risk factors in our study included patients who were relatively younger.…”
Section: Discussionmentioning
confidence: 92%
“…In Wehmeyer's study, it was found that risk factors for VTE include bed rest/restricted mobility > 72 hours and infection. 6 Abdullah Damin conducted a risk assessment of VTE in hospitalized internal medicine patients and found that the most common risk factors for VTE were infection (54.7%), age > 70 years old (38.5%), and heart and/or respiratory failure (21.3%). 7 Mulugeta Asmaw conducted a retrospective study on 219 hospitalized patients in the internal medicine department and found that the probability of VTE in women was more than 14 times higher than that in men ( P = .003).…”
Section: Discussionmentioning
confidence: 99%